2016
DOI: 10.1016/j.jclepro.2015.06.125
|View full text |Cite
|
Sign up to set email alerts
|

Developing eco-innovations: a three-stage typology of supply networks

Abstract: a b s t r a c tThis paper uses grounded theory to develop and deepen our understanding of eco-innovation. It presents, through a series of four propositions, a three-stage supply network typology to help scholars and managers consider how best to develop these innovations. This typology was constructed by reviewing existing sustainability frameworks that argued that innovation was a key factor in sustainability. Moreover we found little consideration given on how to discover and develop eco-innovations. The li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
107
0
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(129 citation statements)
references
References 110 publications
(146 reference statements)
10
107
0
12
Order By: Relevance
“…First, in addition to human capital (Scarpellini, Ortega‐Lapiedra, Marco‐Fondevila, & Aranda‐Usón, ), external resources (Arfi, Hikkerova, & Sahut, ), supply network (Roscoe, Cousins, & Lamming, ) and similar factors found in previous studies, this study found that social capital had an impact on firms' environmental innovations. To be more specific, structural and relational capital played significant, positive roles in environmental innovation, while the role of cognitive capital was not confirmed.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…First, in addition to human capital (Scarpellini, Ortega‐Lapiedra, Marco‐Fondevila, & Aranda‐Usón, ), external resources (Arfi, Hikkerova, & Sahut, ), supply network (Roscoe, Cousins, & Lamming, ) and similar factors found in previous studies, this study found that social capital had an impact on firms' environmental innovations. To be more specific, structural and relational capital played significant, positive roles in environmental innovation, while the role of cognitive capital was not confirmed.…”
Section: Resultssupporting
confidence: 78%
“…First, in addition to human capital (Scarpellini, Ortega-Lapiedra, Marco-Fondevila, & Aranda-Usón, 2017), external resources (Arfi, Hikkerova, & Sahut, 2017), supply network (Roscoe, Cousins, & Lamming, 2016)…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we looked at an output indicator for environmental innovation, instead of input measures on innovative efforts. Eco-innovation shows the real effects, which we find more robust because it reflects tested and specific knowledge of firms and countries (Guo et al, 2017;Roscoe, Cousins, & Lamming, 2016). Previous literature focused on the impact that this type of innovation has on environmental performance, on a firm's reputation and on its market value (Costantini, Crespi, Marin, & Paglialunga, 2017).…”
Section: Mediator Variablementioning
confidence: 59%
“…The use of these evaluation indicators, by taking economic, environmental and social dimensions into account, is expected to help improve and monitor process of product design [75,76]. The proposed MADM approach combines GRA with AHP to rank alternative materials by their economic, environmental, and social performance.…”
Section: Integrated Madm Approach For Materials Selectionmentioning
confidence: 99%